The Effect of Visitor Satisfaction Level on Willingness to Pay at Plengkung, in Alas Purwo National Park - Matondang, Mona Annisa; ., Bahruni; Hermawan, Rachmad (Media Konservasi, 2018)
One of ecotourism destinations in Indonesia is located in the Plengkung Beach at Alas Purwo National Park, Banyuwangi, East Java. Plengkung is one of the world's best locations for surfing activities which can be equated with Hawaii, Australia and South Africa. It was attract tourists to visit Plengkung. Each investor should pay attention to visitor satisfaction in order to maintain and increase the number of visitors. However, visitor satisfaction could be reflected through the improvement of service quality. The purpose of this study was to measure the level of visitor satisfaction based on service quality at PT Plengkung Indah Wisata and PT Wanasari Pramudita Ananta in Plengkung, to measure the value of ecotourism satisfaction using the willingness to pay (WTP) approach and to know the effect of visitor satisfaction level on WTP after doing ecotourism activities. The research was conducted in June-October 2016 with data collection method using quesionnaires, interviews and literature studies. The effect of visitor satisfaction level on WTP of ecotourism activities in Plengkung was analyzed using bivariate correlation analysis (parson correlation coefficient) with p-value